The lipid structure and functional status of blood cells under endogenous intoxication - A P Vlasov; D A Visaitov; V A Trofimov; N U Leschankina; V V Pyanov; V F Mustaytsa (RUDN Journal of Medicine, 2010)
The lipids structure of blood cells and plasma has specific modification under endogenous intoxication. The pathological complex of lipid modification is top-ranked reason of blood cells dysfunction under endogenous intoxication. It is necessary to correct one opportunely.